Security in the Area of Culture as Viewed by the European Union - Gołda-Sobczak, Maria (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2016)
The European Communities, later the European Union, for a long time did not pay attention to the protection of European cultural heritage, as well as to issues of cultural policy, leaving the area more or less consciously the Council of Europe. The cultural policy of the European Union treats the ambiguous term “culture” as an area that belongs to the sphere of national sovereignty. Undefined terms from the area of culture, such as the European cultural space, a common cultural heritage, etc. appear in the documents of the European Union. Only Art. 151 of the Treaty establishing the European Community, currently Art. 167 of the Treaty on the functioning of the European Union is more specifically devoted to the issue of culture and more closely to the issue of heritage. The cultural policy on this ground includes the protection of European cultural heritage, undertaking projects involving the development of a culture and the promotion of Euro¬pean culture. In that respect, the attention should be paid to a number of bilateral agreements, international programs, and finally conventions.

Wspólnoty Europejskie, a później Unia Europejska, przez długi czas nie poświęcały uwagi ochronie europejskiego dziedzictwa kultury, jak i problematyce polityki kulturalnej, pozostawiając ten obszar mniej lub bardziej świadomie systemowi Rady Europy. Polityka kulturalna Unii traktuje wieloznaczny termin kultura jako obszar należący do sfery narodowej suwerenności. W dokumentach unijnych pojawiają się niedefiniowane w praktyce terminy dotyczące obszaru kultury, np. europejska przestrzeń kulturowa, wspólne dziedzictwo kulturowe itd. Zagadnieniu kultury, a ściślej dziedzictwa kulturowego poświęcił uwagę dopiero art. 151 TWE, obecnie art. 167 TFUE. Polityka kulturalna w tej płaszczyźnie obejmuje ochronę europejskiego dziedzictwa kultury, podejmowanie przedsięwzięć polegających na rozwijaniu kultury oraz promocję kultury europejskiej. W kwestiach tych zwrócić należy uwagę na liczne akty o charakterze bilateralnym oraz programy międzynarodowe i konwencje.
Bezpieczeństwo w obszarze kultury w perspektywie Unii Europejskiej
Keywords: culture; European Union law; Treaty on the functioning of the European Union; cultural policy; cooperation in the field of culture; cultural programs; kultura; prawo Unii Europejskiej; Traktat o Funkcjonowaniu Unii Europejskiej; współpraca w dziedzinie kultury; programy kulturalne